2006
DOI: 10.1002/jcp.20675
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of NGF‐signaling and Egr‐1 expression by Tat in neuronal cell culture

Abstract: Examination of signal transduction pathways that modulate neuronal cell differentiation and protection against apoptosis has revealed a central role for the MAPK/Erk cascade. The activation of MAPK/Erk through the TrkA NGF signaling pathway is critical for growth and survival of neuronal cells. Here, we investigate the impact of HIV-1 Tat on the NGF-signaling pathway in SK-N-MC neuroblastoma cells. Expression of Tat decreased cell growth and induced apoptosis. Our results revealed dysregulation of various step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 71 publications
2
10
0
Order By: Relevance
“…Supporting this finding, others have reported that the HIV-Tat protein reduces NGF-stimulated EGR1 expression in SK-N-MC cells, the neuroblastoma cell line used in our studies, acting via inhibition of the MAPK/Erk1/2 pathway (Darbinian-Sarkissian et al, 2006). Since EGR1 is reported as downregulated in models of several other neurodegenerative diseases (Blalock et al, 2003; Booth et al, 2004; Crocker et al, 2006), we asked whether EGR1 downregulation might be a consequence, at least in part, of macrophage/microglia activation present in many of these diseases, rather than the result of SIV infection per se .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Supporting this finding, others have reported that the HIV-Tat protein reduces NGF-stimulated EGR1 expression in SK-N-MC cells, the neuroblastoma cell line used in our studies, acting via inhibition of the MAPK/Erk1/2 pathway (Darbinian-Sarkissian et al, 2006). Since EGR1 is reported as downregulated in models of several other neurodegenerative diseases (Blalock et al, 2003; Booth et al, 2004; Crocker et al, 2006), we asked whether EGR1 downregulation might be a consequence, at least in part, of macrophage/microglia activation present in many of these diseases, rather than the result of SIV infection per se .…”
Section: Discussionsupporting
confidence: 86%
“…Although EGR1 is activated via the MAPK1/2 pathway (Darbinian-Sarkissian et al, 2006) and would therefore be expected to be induced by chemokine stimulation, inhibition of this pathway could occur via “RAF1-AKT crosstalk”, in which RAF1 kinase activity (and downstream MAPK/ERK activation) is suppressed by PKB/AKT phosphorylation of Ser259 in a ligand-, concentration-, and time-course-dependent manner (Zimmermann and Moelling, 1999; Moelling et al, 2002) (Figure 6B). This inhibitory mechanism could be particularly effective after CCL8 stimulation, as it has been reported that binding of CCL8 to CCR2, in contrast to CCL2 binding, fails to induce nuclear translocation of activated ERK1 and downstream gene induction (O’Boyle et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear proteins were extracted and 10 μg were incubated with 50,000 cpm of a [ 32 P]-labeled double-stranded oligodeoxyribonucleotide probe as previously described (Darbinian-Sarkissian et al , 2006; Romagnoli et al , 2008). Probes used in the gel shifts correspond to the BAG3 promoter AP2 site (-146 to −124; 5′-cgcgcccgcccgcggcgactcc-3′) and Ets site (-104 to −79; 5′-tcggaagggggaggcgggaggagg-3′).…”
Section: Methodsmentioning
confidence: 99%
“…ChiP assays used the ChIP assay kit (Upstate Biotechnology, Inc., Lake Placid, NY) as we have previously described (Darbinian-Sarkissian et al , 2006; Gentilella et al , 2008). Briefly, U-87 MG cells were transfected with and without T-Ag expression plasmid for 48h.…”
Section: Methodsmentioning
confidence: 99%
“…SK-N-MC cell lines expressing CFP-Tat and CFP (cyan fluorescent protein) were developed by stably transfecting SK-N-MC cells with CFP-Tat or pECFP-C1 (Clontech, Mountain View, CA) and clonal expression as described previously (Darbinian-Sarkissian et al, 2006). …”
Section: Methodsmentioning
confidence: 99%